The relationship of project management innovation and project performance in Kedah construction industry - Nawawi, Osman (2015)
This study aimed to investigate the relationship of innovation projects and projects under construction Kedah performance. The objective of this study was to categorize the most important element of innovation affect the performance of the project and to identify the relationship between innovation and project performance. The results of the study to see how the attack took place in each of the projects undertaken and how the performance of the project in the event of change as innovations. Therefore, this study aimed to identify whether or not it is an important innovation in every project, and it gets innovations of others to do so. The scope of this study will meet the organization and employees as the unit of analysis of this study, and Kedah in northern Malaysia. Data will be collected from construction companies selected in the state. For data derived from the survey questionnaire and sent via e-mail. The total sample of 50 respondents of 500 construction companies were used in this study. In conclusion, this study has shown that the dependent variable and the dependent variable is related to each other.